Profitability, Leverage, Firm Value through Dividend Policy (Empirical Study on Coal and Lignite Mining Sub-Sector Companies on the IDX 2017-2022) - Suryani, Emma; Sanusi, Fauji; Sunenti, Sunenti (PT. EQUATOR SINAR AKADEMIA, 2024)
This study examines the influence of profitability and leverage on firm value as mediated by dividend policy. The research employs quantitative approaches, examining comparative cause-and-effect links utilizing secondary data from each company's financial records, obtained from either the company's official website or the IDX. This study used a non-probability, purposive sampling technique in coal and lignite subsector companies listed on the IDX from 2017 to 2022, using complete financial data. The research data is panel data examined using Eviews 12 with the subsequent steps of analysis: descriptive statistics, regression model estimation, classical assumptions, panel data regression, and path analysis using the sobel test. The analysis suggests that profitability and leverage have a significant positive effect on firm value, dividend policy has no effect on firm value, profitability has no influence on dividend policy, and leverage increases dividend policy. Consequently, dividend policy cannot mediate the effect of profitability but can mediate the effect of leverage on firm value.